Noninvasive approaches to detect methylation-based markers to monitor gliomas. (11th November 2022) - Noushmehr, Houtan; Herrgott, Grayson; Morosini, Natalia S; Castro, Ana Valeria
Abstract: In this review, we summarize the current approaches used to detect glioma tissue-derived DNA methylation markers in liquid biopsy specimens with the aim to diagnose, prognosticate and potentially track treatment response and evolution of patients with gliomas.